2017
DOI: 10.1007/s00114-017-1507-z
|View full text |Cite
|
Sign up to set email alerts
|

Are the TTAGG and TTAGGG telomeric repeats phylogenetically conserved in aculeate Hymenoptera?

Abstract: Despite the (TTAGG) telomeric repeat supposed being the ancestral DNA motif of telomeres in insects, it was repeatedly lost within some insect orders. Notably, parasitoid hymenopterans and the social wasp Metapolybia decorata (Gribodo) lack the (TTAGG) sequence, but in other representatives of Hymenoptera, this motif was noticed, such as different ant species and the honeybee. These findings raise the question of whether the insect telomeric repeat is or not phylogenetically predominant in Hymenoptera. Thus, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…A few years later, Gokhman et al () also showed absence of this repeat in several superfamilies of parasitoid Hymenoptera including Chalcidoidea. Futhermore, Menezes et al () and Menezes et al () have demonstrated absence of the (TTAGG) n motif in most aculeate Hymenoptera and independent reappearance of this repeat in the families Formicidae and Apidae. Nevertheless, in contrast to Apocrita (=Parasitica + Aculeata), presence of the TTAGG telomeric repeat in the only other existing suborder of this group, i.e., Symphyta, was not investigated until the last years.…”
Section: Telomere Structure In the Class Insectamentioning
confidence: 98%
See 4 more Smart Citations
“…A few years later, Gokhman et al () also showed absence of this repeat in several superfamilies of parasitoid Hymenoptera including Chalcidoidea. Futhermore, Menezes et al () and Menezes et al () have demonstrated absence of the (TTAGG) n motif in most aculeate Hymenoptera and independent reappearance of this repeat in the families Formicidae and Apidae. Nevertheless, in contrast to Apocrita (=Parasitica + Aculeata), presence of the TTAGG telomeric repeat in the only other existing suborder of this group, i.e., Symphyta, was not investigated until the last years.…”
Section: Telomere Structure In the Class Insectamentioning
confidence: 98%
“…On the other hand, Odonata could initially lack the TTAGG telomeric sequence. If this is true, the (TTAGG) n motif independently reappears in S. vulgatum (Kuznetsova et al, ); an analogous situation occurs, e.g., in aculeate Hymenoptera (see Menezes et al, ). An alternative explanation is that this repeat represents a persisting but non‐functional relict of the ancestral telomeric motif/subtelomeric region, as suggested by Korandová et al () for similar cases.…”
Section: Telomere Structure In the Class Insectamentioning
confidence: 99%
See 3 more Smart Citations